2022
DOI: 10.1101/2022.09.19.22279942
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Concurrent and predictive validity of dynamic assessments of word reading in young children: A systematic review and meta-analysis

Abstract: Traditional static literacy assessments evaluate acquired knowledge and are prone to floor effects. These tools are also developed almost exclusively for English monolinguals, and therefore cannot be used equitably to evaluate the abilities of bilingual children. Dynamic assessment (DA), which evaluates the ability to learn a skill, is a potential alternative, and more equitable approach to evaluating critical early literacy skills of phonological awareness, sound-symbols knowledge, and decoding. This systemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(14 citation statements)
references
References 75 publications
(129 reference statements)
2
11
0
Order By: Relevance
“…The review objectives and meta-analytic approach were planned a priori and detailed in a registered protocol on the Open Science Framework. This protocol is available online at https://osf.io/bcghx/ (Wood & Molnar, 2022).…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The review objectives and meta-analytic approach were planned a priori and detailed in a registered protocol on the Open Science Framework. This protocol is available online at https://osf.io/bcghx/ (Wood & Molnar, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Caffrey et al (2008) found that DAs demonstrated greater predictive validity than SA across several domains (e.g., DAs of cognitive ability, literacy, and mathematics). A more recent review focussing exclusively on the domain of word reading skills, reported that DAs of phonological awareness and decoding demonstrate concurrent validity with SAs and predictive validity with word reading outcomes (Wood et al, 2023). In terms of format of DAs of word reading skills, no quantitative comparison has been conducted evaluating differences in associations with word reading outcomes, although findings suggest that there are no differences in classification accuracy of reading disorder for DAs that use a GP vs. TT format (Dixon et al, 2022b)).…”
Section: Previous Research In Dynamic Assessment Of Word Reading Skillsmentioning
confidence: 99%
See 3 more Smart Citations